Non-intubated uniportal video-assisted thoracoscopic surgery for carinal sleeve resection—is surgical process almost completed? - Herrmann, Dominik; Volmerig, Jan; Hecker, Erich (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Fortunately, Bernhard von Langenbeck was wrong when he gave the opening speech at the first congress of German society of surgery in 1872 and declared the surgical process to be almost completed (1).